Reduction of Salmonella Typhimurium on Poultry Skin Utilizing Sodium Metasilicate in Prechill and Postchill Applications - Mart, S.; Williams , S.K.; Sharma, C.S. (International Journal of Poultry Science, 2013)
The comparison of antimicrobial properties of sodium metasilicate (SMS) to conventional chlorine applications in pre and postchill processing of poultry was evaluated. Fresh broiler chicken breast skin was cut aseptically into 5x5 cm portions and treated with either water only (negative control), inoculum+water (positive control, 107 cfu/mL of Salmonella Typhimurium), inoculum +50 ppm chlorine solution, inoculum +2% SMS solution, inoculum +2% SMS solution followed by 50 ppm chlorine solution (prechill), or inoculum +50 ppm chlorine solution followed by 2% SMS solution (postchill) and analyzed after 0 and 24 h storage at 4°C for Salmonella spp., total plate count and pH. Sodium metasilicate postchill treatment reduced aerobic plate counts at 0 and 24 h by 2.97 and 5.31 logs, respectively and Salmonella spp. counts at 0 and 24 h by 5.82 and 6.47 logs, respectively. The data revealed that SMS was most effective as postchill treatment. This research revealed the possibility of sodium metasilicate being used as an antimicrobial intervention in poultry chill tanks to control Salmonella.